Poltergeist (1982) [videorecording (DVD)] - Hooper, Tobe, 1943-2017; Spielberg, Steven, 1946-; Williams, JoBeth; Nelson, Craig T.; Straight, Beatrice; Dunne, Dominique, 1959-1982; Robins, Oliver, 1971- (Distributed by Warner Home Video, 2007)
The Freeling family is a typical middle class family living in the peaceful Cuesta Verde Estates. Steve, his wife Diane, 16-year-old daughter Dana, 8-year-old Robbie, and 5-year-old Carol Ann live in a tract house. Soon strange things begin to happen around the house; the pet canary dies, mysterious storms occur, and Carol Ann is summoned to the TV set, where a strange shaft of green light hits her and causes the room to shake. As the curious events continue, Carol Ann is repeatedly drawn to the television, where she begins to talk to "the TV people." Soon Carol Ann is sucked into a closet, disappearing from this reality plane. Unable to find his daughter, Steve consults Dr. Lesh, a para-psychologist from a nearby college. Lesh finds that the paranormal phenomena is so strong in the Freelong household she is unable to deal with it and sends for clairvoyant and professional exorcist Tangina to examine the house in hopes of finding Carol Ann. Tangina makes a horrifying discovery: Carol Ann is alive and in the house, but is being held on another spectral plane.